Simultaneous recordings from vestibular Type I hair cells and their calyceal afferents in mice - Contini, Donatella; Holstein, Gay R.; Art, Jonathan J. (Frontiers in Neurology, 2024)
The vestibular hair cell receptors of anamniotes, designated Type II, are presynaptic to bouton endings of vestibular nerve distal neurites. An additional flask-shaped hair cell receptor, Type I, is present in amniotes, and communicates with a chalice-shaped afferent neuritic ending that surrounds the entire hair cell except its apical neck. Since the full repertoire of afferent fiber dynamics and sensitivities observed throughout the vertebrate phyla can be accomplished through Type II hair cell-bouton synapses, the functional contribution(s) of Type I hair cells and their calyces to vestibular performance remains a topic of great interest. The goal of the present study was to investigate electrical coupling between the Type I hair cell and its enveloping calyx in the mouse semicircular canal crista ampullaris. Since there are no gap junctions between these two cells, evidence for electrical communication would necessarily involve other mechanisms. Simultaneous recordings from the two cells of the synaptic pair were used initially to verify the presence of orthodromic quantal synaptic transmission from the hair cell to the calyx, and then to demonstrate bi-directional communication due to the slow accumulation of potassium ions in the synaptic cleft. As a result of this potassium ion accretion, the equilibrium potentials of hair cell conductances facing the synaptic cleft become depolarized to an extent that is adequate for calcium influx into the hair cell, and the calyx inner face becomes depolarized to a level that is near the threshold for spike initiation. Following this, paired recordings were again employed to characterize fast bi-directional electrical coupling between the two cells. In this form of signaling, cleft-facing conductances in both the hair cell and calyx increase, which strengthens their coupling. Because this mechanism relies on the cleft resistance, we refer to it as resistive coupling. We conclude that the same three forms of hair cell-calyceal transmission previously demonstrated in the turtle are present in the mammalian periphery, providing a biophysical basis for the exceptional temporal fidelity of the vestibular system.